The impact of COVID-19 pandemic restrictions on offline and online grocery shopping: New normal or old habits? - Philipp Brüggemann; Rainer Olbrich (Electronic Commerce Research, 2022)
The COVID-19 pandemic is changing future trends in retailing and e-commerce immensely. Recent research revealed a considerable increase in online grocery shopping (OGS) since the COVID-19 pandemic started. In addition, current statistics indicate a steady increase in OGS over the coming years. Despite this, less is known about whether consumers' behavior is evolving to a 'new normal' or returning to 'old habits' after pandemic restrictions are withdrawn. To address this research gap, we operationalize and empirically analyze offline and online purchasing behavior before, during, and after pandemic restrictions. To this end, we use an extensive household panel dataset of 17,766 households reporting their purchases before, during and after the first lockdown in Germany in 2020. Our findings on offline purchase patterns show that while more than 10% of the consumers avoided brick-and-mortar retail during the lockdown, almost all of them returned afterwards. Looking at online purchase patterns, we find high volatility in OGS for both separate and combined purchase patterns. The combined analysis of purchase patterns (online and offline), reveal that households that avoided brick-and-mortar stores during the lockdown did not switch (completely) to the online channel. Based on our findings that consumers are still in reach of brick-and-mortar retailers we suggest offline retailers act now to retain their customers, e.g., by offering competitive benefits in their stores. OGS operators should urgently analyze the customer churn revealed in this analysis and derive measures to retain them. They do not seem to have succeeded in retaining their customers and keeping them loyal to the online channel during the entire observation period. Even worse, they also failed to convince consumers to use OGS who stayed at home due to the lockdown. The fact that a total of 96.75% of the observed consumers did not practice OGS at all shows that OGS in Germany was in 2020 still in its infancy. However, as current statistics forecast a further substantial increase in OGS over the coming years, our results are increasingly relevant for brand managers, brick-and-mortar retailers and OGS providers in Germany and beyond.
Keywords: 380; New normal; Old habits; Online grocery shopping; Pandemic restrictions; Purchase pattern; Retail